Combined effects of ultraviolet radiation and temperature on morphology, photosynthesis, and DNA of Arthrospira (Spirulina) Platensis (Cyanophyta) - Gao, Kunshan (2008)
Natural levels of solar UVR were shown to break and alter the spiral structure of Arthrospira (Spirulina) platensis (Nordst.) Gomont during winter. However, this phenomenon was not observed during summer at temperatures of 30C. Since little has been documented on the interactive effects of solar UV radiation (UVR; 280?400 nm) and  temperature on cyanobacteria, the morphology, photosynthesis, and DNA damage of A. platensis were examined using two radiation treatments (PAR [400?700 nm] and PAB [PAR + UV-A + UV-B: 280?700]), three temperatures (15, 22, and 30C), and three biomassconcentrations (100, 160, and 240 mg dwt [dry weight] Æ L)1). UVR caused a breakage of the spiral structure at 15C and 22C, but not at 30C. High PAR levels also induced a significant breakage at 15C and 22C, but only at low biomass densities, and to lesser extent when compared with the PAB treatment. A. platensis was able to alter its spiral structure by increasing helix tightness at the highest temperature tested. The photochemical efficiencywas depressed to undetectable levels at 15C but was relatively high at 30C even under the treatment with UVR in 8 h. At 30C, UVR led to 93%?97% less DNA damage when compared with 15C after 8 h of exposure. UV-absorbing compounds were determined as negligible at all light and temperature combinations. The possible mechanisms for the temperature-dependent effects of UVR on this organism are discussed in this paper.